The effects of substituent position on kinetics of benzene vapour adsorption onto 3-phenylphenoxy substituted metal-free and metallo-phthalocyanines thin films - ALTUN, SELÇUK; ODABAŞ, ZAFER (ROYAL SOC CHEMISTRY, 2016)
The preparation of metal-free, Zn(II), In(III), and Cu(II)-phthalocyanines containing tetrakis-(3-phenylphenoxy) groups was achieved by employing 3-(3-phenylphenoxy)phthalonitrile (1) and 4-(3-phenylphenoxy)phthalonitrile (2) as starting materials. The phthalonitriles and phthalocyanines were characterized by elemental analysis, infrared, proton nuclear magnetic resonance, ultraviolet-visible, and matrix-assisted laser desorption/ionization time-of-flight mass spectroscopic techniques. The effect of the substituent group on the kinetics of benzene vapour adsorption onto these novel compounds was examined using three kinetics models: the pseudo first-order model, the Elovich equation, and a simple adsorption-desorption model. Results show that the benzene adsorption kinetics strongly depend on the position of the substituent groups.
Keywords: GAS-SENSING PROPERTIES; TEMPERATURE; HOMO